CHOOSING THE GENITORS - AN IMPORTANT MEASURE IN MAKING THE BREEDING WORKS BETTER AT THE SPRING BARLEY - Ioana PORUMB; Florin RUSU; Ancuța BOANTA; Emanuela FILIP; Nicolae TRITEAN; Cristina STANCĂ-MOISE; Leon MUNTEAN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Ensuring progress in improving barley's production and traits of interest is closely linked to the diversity and performance of the original material that can lead to increased genetic variability and new valuable cultivars. Thus, phenotyping of the genotyping collection is a first step in identifying the most valuable available genres and introducing them into hybridization programs, depending on the complementarity of the traits. The traits that have been quantified and used to determine the cognition degree of the cultivars studied are: plants height, ear length, number of grain / ear, grain weight/ear, TKW, protein and starch content. Genotypes have been identified that can be used in future amelioration works either to increase the fall resistance because plants height value are approximately 81 cm or for qualitative improvement, showing high TKW values (52 g), low content protein (less than 10.5%) and high starch content (approximately 60%).